Pertumbuhan Dan Hasil Tanaman Kacang Buncis (Phaseolus vulgaris L.) Akibat Pemberian Beberapa Takaran Kascing - Habib Maulana; Sevindrajuta Sevindrajuta; Chika Sumbari (CULTIVATE: Journal of Agriculture Science, 2025)
Research in the form of a field experiment entitled "Growth and yield of green bean plants (Phaseolus vulgaris L.) due to the provision of several doses of vermicompost", was carried out at the Experimental Garden of the Faculty of Agriculture, University of Muhammadiyah West Sumatra, Tanjung Gadang Koto Nan Ampek Village, Payakumbuh Barat District, Payakumbuh City, with Inceptisol soil type, and has an altitude of ± 514 meters above sea level. The implementation of this experiment started from June to August 2023. This study was conducted using a Randomized Block Design (RAK) where there were 5 treatments and 4 groups, so that a total of 20 experimental plots each plot contained 6 plants taken 2 plants as sample plants. with a plot size of 1 m x 1.2 m, with the following treatments, namely vermicompost doses. 0 tons / ha, 2 tons / ha, 4 tons / ha, 6 tons / ha, and 8 tons / ha. Data from observations of green beans were averaged and analyzed statistically with the F test at a significance level of 5%. The observation parameters carried out were Field Emergence Time (days), Plant Height (cm), Flowering Age (days), Harvest Age (days), Number of Pods Per Plant (pods), Pod Weight Per Plant (g), Pod Weight per Plot (kg), and Pod Weight per Hectare (tons). From the results of this study, it can be concluded that the provision of several doses of vermicompost has not been able to increase the growth and yield of green bean plants